Insect Pests of Stored Legumes problems and prospects - Srivastava, Chitra; Sagar, D (Indian Farming, 2018)
In the storage pest management, as an alternative to chemical fumigants, the eco-friendly prophylactic and curative approaches like timely harvesting and sun drying of legumes, use of inert dusts to protect grains, application of vegetable oils to prevent egg laying in storage and use of pheromones for monitoring and mass trapping of storage pests plays an important role.